(untitled) (AYUSHDHARA, 2020)
Hand sanitizers are used to ensure hygiene in the absence of hand washing facilities or where frequent sanitizing is required especially in the wake of the Covid-19 pandemic. Handsanitizers using different combinations were prepared at Oushadhi using WHO recommendations and also to promote Kerala Government’s initiative of break the chain campaign. The campaign was launched on 15th March 2020 and it aims to cut down the progress of disease transmission. The efficacy of the batches of sanitizers prepared was tested against Escherichia coli and Staphylococcus aureus. They were also tested against common air and water contaminants found in the premises which would be of more significance to the general workforce. The susceptibility test was performed by agar well diffusion method and it revealed that the antimicrobial efficacy of the prepared hand sanitizer Batch III with Cymbopogon citratus oil was the most effective among the three combinations. A hedonic sensory evaluation was carried out for better consumer acceptability.